Private security’s accountabilities within polycentric assemblages - Berg, Julie (International journal of comparative and applied criminal justice, 2022)
This article will reflect on the multiple ways in which private security can, and is, being held responsible and accountable to the public (and other security providers), in formalised, polycentric, or nodal assemblages. Drawing on empirical research conducted on plural policing partnerships, the article will show that private security is influenced by market forces, but that this is part of an interwoven, layered, formal-informal system of accountabilities – most of which are bottom-up and relational, rather than top-down and legislated. In fact, drawing on the work of John Braithwaite, we show that horizontal or circular forms of accountability (or accountabilities) play a large role in aligning the private sector to the public interest or common good within pluralised environments.